The Role of Job Satisfaction in Mediating the Influence of Occupational Health & Safety (K3) and Work Environment on Employee Performance at PT. Margaria Group Yogyakarta. - Utari, Febby Tri; Subyantoro, Arief (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
The type of research that researchers conducted was quantitative research which aimed to determine the effect of Occupational Health & Safety and Work Environment on Employee Performance with Job Satisfaction as a mediating variable. The sample used in this study were general affairs employees at PT. Margaria Group Yogyakarta with 50 employees. The sampling technique was carried out using non-probability sampling with saturated sampling method. Data collection was carried out using a questionnaire. The analysis technique used in this research is path analysis. The results of this study conclude that Occupational Health & Safety has a positive and significant effect on Employee Performance and the Work Environment has a positive and significant effect on Employee Performance. Occupational Health & Safety and Work Environment have a significant effect on Employee Performance indirectly through Job Satisfaction as a mediating variable.